Voices of teachers: a qualitative analysis of the feasibility and qualitative perceptions of impact of SEE Learning on the well-being of Ukrainian classrooms before and during war - Tyralynn Frazier; Sara Rosenstein; Oleksandr Elkoin; Oleg Marushchenko; Natalia Rudzynska; Tetiana Drozhzhina (Conflict and Health)
Abstract Background This study investigates the feasibility and qualitative impact of SEE Learning, a school-based Social and Emotional Learning (SEL) program, on the well-being of Ukrainian classrooms amidst war. By prioritizing children’s social and emotional development and access to quality education during conflict, this research aims to understand the potential contribution of compassion-based training programs to building sustainable pathways toward peace. Methods Twenty-three implementing teachers participated in in-depth interviews about SEE Learning implementation and impact. The interviews were conducted in Ukrainian, translated into English, and de-identified for analysis. Data was coded by primary and secondary coders, with agreement determined and analyzed through thematic analysis. Results Teachers expressed the need for SEE Learning in their classrooms during war. They viewed SEE Learning implementation during war as more important than before the 2022 Russian invasion, allocating extra class time to engage in SEE Learning-specific activities. The program helped teachers cultivate a safe and supportive space for processing difficult emotions brought on by war. Its implementation supported teachers’ personal and professional development alongside the building of students’ social-emotional skills. Teachers noticed that students were better able to identify and understand their emotions and the emotions of others, creating a more compassionate and productive classroom environment. Conclusions SEE Learning shows promise in helping teachers create safe, supportive environments and address students’ emotional needs in high-conflict contexts. Further research and culturally specific implementations are essential to enhance psychosocial support and resilience in such challenging settings.